2018
DOI: 10.3389/fnhum.2018.00231
|View full text |Cite
|
Sign up to set email alerts
|

Neurophysiological Measures of the Perception of Antismoking Public Service Announcements Among Young Population

Abstract: Tobacco constitutes a global emergency with totally preventable millions of deaths per year and smoking-related illnesses. Public service announcements (PSAs) are the main tool against smoking and by now their efficacy is still assessed through questionnaires and metrics, only months after their circulation. The present study focused on the young population, because at higher risk of developing tobacco addiction, investigating the reaction to the vision of Effective, Ineffective and Awarded antismoking PSAs th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

5
4

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 166 publications
(198 reference statements)
0
26
0
Order By: Relevance
“…It could be hypothesized that possible different cerebral patterns could be obtained in response to different kinds of effective (e.g., successful) or ineffective PSAs or in the perception of the consumer's gender differences during the observation of charity campaigns by using neurophysiological measurements, such as EEG [240]. Therefore, obtaining measurable neurophysiological parameters, collected through direct analysis of the measured cerebral/emotional/visual attention (VA) in response to the observation of PSAs, represents an important question [73]. PSAs are at the core of many public health campaigns against smoking, junk foods, abuse of alcohol, and other possible threats to the health of citizens.…”
Section: Value Proposition and Marketing Operation: How Neuromarkementioning
confidence: 99%
“…It could be hypothesized that possible different cerebral patterns could be obtained in response to different kinds of effective (e.g., successful) or ineffective PSAs or in the perception of the consumer's gender differences during the observation of charity campaigns by using neurophysiological measurements, such as EEG [240]. Therefore, obtaining measurable neurophysiological parameters, collected through direct analysis of the measured cerebral/emotional/visual attention (VA) in response to the observation of PSAs, represents an important question [73]. PSAs are at the core of many public health campaigns against smoking, junk foods, abuse of alcohol, and other possible threats to the health of citizens.…”
Section: Value Proposition and Marketing Operation: How Neuromarkementioning
confidence: 99%
“…[75][76][77][78]). Also, in the context of social campaigns (concerning anti-smoking announcements), Cartocci et al [79] have shown-to some extent-a positive relationship between campaign effectiveness and approach motivation indicated by the frontal asymmetry among smokers.…”
Section: Brain Oscillations As a Marker Of Neural Reactions To Socialmentioning
confidence: 99%
“…Therefore, if in the 60s an EEG device required a room and meters of cables, modern EEG devices are no larger than a smartphone and equipped with storage support, long-life batteries and wireless communication. These great improvements are at the basis of the recent successes of cognitive and behavioral neuroscience research, since it is now possible to investigate human brain physiological dynamics while working or performing everydayness activities, such as driving the car [7,8,9] or piloting an aircraft [10,11,12], working in control rooms [13,14,15,16], watching the TV [17,18], doing sport [19], eating [20], listening music [21,22] or smelling fragrances [23,24]. EEG devices are now wearable and they are considered the key tool to bring research about Brain-Computer Interfaces (BCI, i.e., those system aimed to adapt the objects behavior on the basis of current human mental states) from the laboratory to the applicative fields [25,26].…”
Section: Introductionmentioning
confidence: 99%